The Innovation of Teaching based on Technology: Improving Educational Quality in Digital Era - Doni Suganda Putra; Ulil Arham; Aldino Gusto; Dayu Okta Putra; Adi Fitra Andikos (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
To complete the research answer on the topic of producing digital learning to improve the quality of student learning in the era of the technological revolution 4.0 at STITNU Sakinah Dharmasraya, researchers have collected various materials that answer research questions. Likewise, to collect primary data, researchers interviewed 30 academics (students and lecturers) of STITNU Sakinah Dharmasraya to find out their perspectives and experiences in developing digital-based teaching to improve student learning outcomes during regular education and throughout education. Therefore, a review of different data sets was carried out, both in the form of secondary source data from various publications related to technology and teaching as well as data that researchers asked academics to find answers to. Researchers can simplify the development of digital teaching to improve the quality of student learning in the Revolution 4.0 era at STITNU Sakinah Dharmasraya. This has resulted in several new insights, such as technology has innovated the learning process because digital applications have helped academics solve learning challenges and provide more benefits. They hope that these findings can provide new insights into learning in higher education and their use in policy making